Categorizing households into different food security states in Nigeria: the socio-economic and demographic determinants - Kolawole Ogundari (Agricultural and Food Economics, 2017)
The literature reiterates the need to employ indicators that reflect the multidimensional nature of food security. In a quest to capture the multidimensional nature of food security, this study uses a novel ideal that harmonizes two food security indicators (food expenditure (FOODexp) and dietary diversity score (DDS)) to categorize households into different levels of food security states in Nigeria. In addition, the study also examined factors that influence the probability of households being in different levels of food security states in the country. Our estimates show that about 66 and 60% of the households in the sample were food secure based on a single indicator such as FOODexp and DDS, respectively. However, by harmonizing the two indicators, results reveal that about 42% of the households are actually food secure. The implication of this is that about 24 and 18% of the households are transitory food insecure. Results also suggest that the use of a single indicator may wrongly classify households as food secure instead of categorizing them as transitory food insecure. Furthermore, the empirical results show that households that consume only home produced food have high probabilities of being food insecure, while households that consume only market-purchased food are less likely to be food insecure. The implication of this finding is that harmonization of food security indicators helps identify households with different nature of food (in) security problems that require different types of policy interventions most especially in Nigeria. The results of the empirical analysis also imply that market-based intervention policies that facilitate households' access at all time to healthy foods of their choice should be given priority. This gives the household opportunity to benefit from greater varieties of food items offered by the market.
Keywords: D12; D13; Q12; 330; Dietary diversity; Food security; Food expenditure; Determinants; Household; Nigeria